Vegetation analysis and plant diversity in Pinus Jantho Forest (PJF) nature reserve, Aceh Besar - HILMINA ITAWAMERNI; SAIDA RASNOVI; ZUMAIDAR ZUMAIDAR (Jurnal Natural, 2021)
Pinus Jantho Forest (PJF) Nature Reserve has unique characteristics and distinctive ecosystem that plays an important role in the preservation of germplasm and the protection of natural resources. The sustainability of the PJF Nature Reserve is strongly determined by vegetation of its constituents. Therefore, an effort is needed to help its management properly, one of which is by knowing the diversity of plants that make up the community in PJF Nature Reserve. The purpose of this research is to analyze the composition and diversity of plant species in PJF Nature Reserve. Data collection and sampling were done using multiple square method. The plots were laid out by systematic sampling. PJF Nature Reserve composed of 111 species from 46 family. The seedling and understorey have the highest number individuals (1028 in total). Then there are 240 individuals at sapling level, 108 individuals at pole, and 72 individuals for tree.  The Euphorbiaceae family has the largest number of species (11 species). The highest Important Value Index (IVI) for seedlings and understorey, sapling and pole, and tree respectively were Chloranthus elatior (11.09%), Piper aduncum (21.90% and 19.32%), and Pinus merkusii (25.52%). The Diversity Index indicates a high level of plant species diversity (3.25-3.63).